Data quality control considerations in multivariate environmental monitoring: experience of the French coastal network SOMLIT - Elsa Breton; Nicolas Savoye; Peggy Rimmelin-Maury; Benoit Sautour; Eric Goberville; Arnaud Lheureux; Thierry Cariou; Sophie Ferreira; Hélène Agogué; Samir Alliouane; Fabien Aubert; Sébastien Aubin; et al. (Frontiers in Marine Science, 2023)
Introduction While crucial to ensuring the production of accurate and high-quality data—and to avoid erroneous conclusions—data quality control (QC) in environmental monitoring datasets is still poorly documented. Methods With a focus on annual inter-laboratory comparison (ILC) exercises performed in the context of the French coastal monitoring SOMLIT network, we share here a pragmatic approach to QC, which allows the calculation of systematic and random errors, measurement uncertainty, and individual performance. After an overview of the different QC actions applied to fulfill requirements for quality and competence, we report equipment, accommodation, design of the ILC exercises, and statistical methodology specially adapted to small environmental networks (<20 laboratories) and multivariate datasets. Finally, the expanded uncertainty of measurement for 20 environmental variables routinely measured by SOMLIT from discrete sampling—including Essential Ocean Variables—is provided. Results, Discussion, Conclusion The examination of the temporal variations (2001–2021) in the repeatability, reproducibility, and trueness of the SOMLIT network over time confirms the essential role of ILC exercises as a tool for the continuous improvement of data quality in environmental monitoring datasets.

Interoperable vocabulary for marine microbial flow cytometry - Melilotus Thyssen; Gérald Grégori; Véronique Créach; Soumaya Lahbib; Mathilde Dugenne; Hedy M. Aardema; Luis-Felipe Artigas; Bangqin Huang; Aude Barani; Laureen Beaugeard; Amel Bellaaj-Zouari; Alfred Beran; et al. (Frontiers in Marine Science, 2022)
The recent development of biological sensors has extended marine plankton studies from conducting laboratory bench work to in vivo and real-time observations. Flow cytometry (FCM) has shed new light on marine microorganisms since the 1980s through its single-cell approach and robust detection of the smallest cells. FCM records valuable optical properties of light scattering and fluorescence from cells passing in a single file in front of a narrow-collimated light source, recording tens of thousands of cells within a few minutes. Depending on the instrument settings, the sampling strategy, and the automation level, it resolves the spatial and temporal distribution of microbial marine prokaryotes and eukaryotes. Cells are usually classified and grouped on cytograms by experts and are still lacking standards, reducing data sharing capacities. Therefore, the need to make FCM data sets FAIR (Findability, Accessibility, Interoperability, and Reusability of digital assets) is becoming critical. In this paper, we present a consensus vocabulary for the 13 most common marine microbial groups observed with FCM using blue and red-light excitation. The authors designed a common layout on two-dimensional log-transformed cytograms reinforced by a decision tree that facilitates the characterization of groups. The proposed vocabulary aims at standardising data analysis and definitions, to promote harmonisation and comparison of data between users and instruments. This represents a much-needed step towards FAIRification of flow cytometric data collected in various marine environments.

Multiple phytoplankton community responses to environmental change in a temperate coastal system: A trait-based approach - Elsa Breton; Eric Goberville; Benoit Sautour; Anis Ouadi; Dimitra-Ioli Skouroliakou; Laurent Seuront; Gregory Beaugrand; Loïck Kléparski; Muriel Crouvoisier; David Pecqueur; Christophe Salmeron; Arnaud Cauvin; et al. (Frontiers in Marine Science, 2022)
The effect of environmental change in structuring the phytoplankton communities of the coastal waters of the Eastern English Channel was investigated by applying a trait-based approach on two decades (1996-2019) of monitoring on diatoms and Phaeocystis . We show that phytoplankton species richness in an unbalanced nutrient supply context was influenced by wind-driven processes, ecological specialization for dissolved inorganic phosphorous, temporal niche differentiation, and a competition-defense and/or a growth-defense trade-off, a coexistence mechanism where weak competitors (i.e., slower growing) are better protected against predation. Under the influence of both environmental perturbations (e.g., wind-driven processes, freshwater influence, unbalanced nutrient levels) and biotic interactions (e.g., competition, predation, facilitation), phytoplankton species exhibited specific survival strategies such as investment on growth, adaptation and tolerance of species to environmental stresses, silicification and resource specialization. These strategies have led to more speciose communities, higher productivity, functional redundancy and stability in the last decade. Our results revealed that the unbalanced nutrient reduction facilitated Phaeocystis blooms and that anthropogenic climate warming and nitrate reduction may threaten the diatom communities of the eastern English Channel in a near future. Our results provide strong support for biogeographical historical and niche-based processes in structuring the phytoplankton community in this temperate region. The variety of species responses that we characterized in this region may help to better understand future changes in pelagic ecosystems, and can serve as a basis to consider functional approaches for future ecosystem management.

Seasonal Variations in the Biodiversity, Ecological Strategy, and Specialization of Diatoms and Copepods in a Coastal System With Phaeocystis Blooms: The Key Role of Trait Trade-Offs - Elsa Breton; Urania Christaki; Benoit Sautour; Oscar Demonio; Dimitra-Ioli Skouroliakou; Gregory Beaugrand; Laurent Seuront; Loïck Kléparski; Adrien Poquet; Antoine Nowaczyk; Muriel Crouvoisier; Sophie Ferreira; et al. (Frontiers in Marine Science, 2021)
Although eutrophication induced by anthropogenic nutrient enrichment is a driver of shifts in community composition and eventually a threat to marine biodiversity, the causes and consequences on ecosystem functioning remain greatly unknown. In this study, by applying a trait-based approach and measuring niche breadth of diatoms and copepods, the drivers and underlying mechanisms of the seasonal species succession of these ecological communities in a coastal system dominated in spring by Phaeocystis blooms were explored. It is suggested that the seasonal succession of diatoms and copepods is the result of several trade-offs among functional traits that are controlled by the seasonal abiotic and biotic pressure encountered by the plankton communities. The results of this study highlight that a trade-off between competition and predator, i.e., weak competitors are better protected against predation, plays an important role in promoting plankton species richness and triggers the Phaeocystis bloom. As often observed in eutrophicated ecosystems, only the biotic homogenization of the copepod community and the shift in the diet of copepods toward Phaeocystis detrital materials have been detected during the Phaeocystis bloom. The diatom and copepod communities respond synchronously to fluctuating resources and biotic conditions by successively selecting species with specific traits. This study confirms the key role of competition and predation in controlling annual plankton succession.

Effects of experimental warming on small phytoplankton, bacteria and viruses in autumn in the Mediterranean coastal Thau Lagoon - Justine Courboulès; Francesca Vidussi; Tanguy Soulié; Sébastien Mas; David Pecqueur; Behzad Mostajir (Aquatic Ecology, 2021)
To investigate the responses of a natural microbial plankton community of coastal Mediterranean waters to warming, which are still poorly known, an in situ mesocosm experiment was carried out in Thau Lagoon during autumn 2018. Several microorganisms, including virio-, bacterio-, and phytoplankton Prochlorococcus -like and Picochlorum -like cells, which had not previously been found in Thau Lagoon. The experimental warming treatment increased the abundances of nanophytoplankton, cyanobacteria, bacteria and viruses during the experiment and triggered earlier blooms of cyanobacteria and picoeukaryotes. Only the abundance of Picochlorum -like cells was significantly reduced under warmer conditions. The growth and grazing rates of phytoplankton and bacterioplankton estimated on days 2 and 8 showed that warming enhanced the growth rates of most phytoplankton groups, while it reduced those of bacteria. Surprisingly, warming decreased grazing on phytoplankton and bacteria at the beginning of the experiment, while during the middle of the experiment it decreased the grazing on prokaryote only but increased it for eukaryotes. These results reveal that warming affected the Thau Lagoon plankton community from viruses to nanophytoplankton in fall, inducing changes in both dynamics and metabolic rates.

Dynamics of microbial planktonic food web components during a river flash flood in a Mediterranean coastal lagoon - David Pecqueur; Francesca Vidussi; Eric Fouilland; Emilie Le Floc’h; Sebastien Mas; Cecile Roques; Christian Salles; Marie-George Tournoud; Behzad Mostajir (Hydrobiologia, 2011)